Specificity of plant-odor detecting olfactory sensory neurons in Ctenarytaina eucalypti (Homoptera: Psylloidea) - Yuvaraj,Jothi Kumar (2012)
Abstract The blue gum psyllid, Ctenarytaina eucalypti (Homoptera: Psylloidea), is an economic threat to Eucalyptus plantations worldwide. To date, no efficient control method is available for this pest and the potential for semiochemical-based monitoring or control methods have not yet been investigated. Hence, I conducted the first study on the olfactory sense of C. eucalypti, investigating the specificity of host odor detecting olfactory sensory neurons (OSNs) using single sensillum recordings (SSR). Synthetic compounds were selected after analysis of headspace collections from Eucalyptus. Ctenarytaina eucalypti has four sensillar cavities (S1-S4) containing olfactory sensilla. My recordings revealed that each of these sensilla houses three OSNs that could be distinguished based on spike amplitude. OSN (A-neuron) in sensillum S1 responded strongly to linalool and weakly to β-caryophyllene and β-ocimene. Furthermore, OSN (B-neuron) of both sensilla S2 and S3 showed strong response to 1-hexanol, Z3-hexenol, and Z3-hexenyl acetate. OSNs in sensillum S4 showed only weak responses to some of the synthetic compounds tested. The physiologically active volatiles may be used by C. eucalypti for long-range host finding. Future experiments in the laboratory and in the field will reveal if this hypothesis is correct and indicate if plant volatiles can be used in detection and monitoring of C. eucalypti populations. Popular science summary: Volatile cues in blue gum psyllid host location Psyllids or 'jumping plant lice' are tiny phytophagous, phloem feeding insects. Psyllids together with aphids, coccids and whiteflies comes under the suborder Sternorrhyncha (Order: Homoptera). The psyllids can feed on a single plant (monophagous) or related plants (oligophagous). Many psyllid species are known to cause damage to agriculture and forest plantations, among those Ctenarytaina eucalypti (Blue gum psyllid) is causing damge to Eucalyptus plantations. The blue gum psyllids are affecting the commercial production of cut foliage by feeding on the leaves and transmitting viruses. Current control methods for eucalyptus psyllids are not sufficient. In order to control this pest by using volatile compounds as attractant or repellent, I did the first study on finding volatile cues used by the blue gum psyllid (Ctenarytaina eucalypti) to locate their food/host. The headspace (air around the plant) of Eucalyptus was collected and analysed using gas chromatography coupled mass spectrometry. The identified compounds were used to check the physiological response of psyllids. The olfactory sensory neurons (OSNs) of insects are used to sense the volatile compounds. Using a device called single sensillum recording, I recorded the OSNs response of psyllids to the headspace volatile compounds of Eucalyptus. What psyllids use to find food? When testing the physiological response of psyllids, they responded strongly to linalool, 1-hexanol, Z3-hexenol and Z3-hexenyl acetate. All the compounds that gave response here were already reported to have a behavioural role in insect host location in many insect species. They have been reported as positive or negative olfactory cues where it provides information about the host or unsuitable host. Here I found linalool, 1-hexenol, Z3-hexenol and Z3-hexenyl acetate elicited strong response and some other compounds showed weak response physiologically. To know their behavioural role in eucalyptus psyllids, more behavioural experiments will be conducted in future. Advisor: Martin N. Andersson and Olle Anderbrant Master´s Degree Project 45 credits in Chemical Ecology, 2012 Department of Biology, Lund University